Clinico-Pathological Features of Newcastle Disease in Japanese Quails (Coturnix coturnix japonica) Infected with Newcastle Disease Virus Kudu 113 Strain - Oladele, Sunday Blessing; Enoch, Ishiaku; Lawal, Sa`idu; Ibu, O.J. (International Journal of Poultry Science, 2008)
Experiments were performed to determine whether Japanese quails (Coturnix coturnix japonica) are susceptible to Newcastle disease virus (NDV) Kudu 113 strain. In the experimental trials, a total 119, six weeks old Japanese quails were administered varying doses of the virus, ranging from 0.1 ml to 0.3 ml intramuscularly (im) and per os (po). The uninfected control quails were not administered the virus and were reared separately. Depression, weakness, incoordination, anorexia, ruffled feathers and paralysis of legs and wings were noted in some of the infected quails. At necropsy, some of the infected quails also had haemorrhagic enteritis and congested lungs, liver, heart and spleen and muscles of breast, thighs and legs. There was a rise in haemagglutination inhibition (HI) antibody titre in all the infected quails, following administration of NDV Kudu 113 strain either im or po. The highest mean HI antibody titre of log2 10.56± 0.29 was obtained on day seven post infection (pi) in the group that was administered 0.3 ml of the virus im. Similarly, the highest mean HI antibody titre of log2 9.89±0.48 was obtained on day seven pi in quails that were administered 0.3 ml of the virus po. On the other hand, the control quails were negative to HI antibody test. This study demonstrated that Japanese quails are susceptible to NDV Kudu 113 strain.